A new control unit for probing ion beam forming in HIBP diagnostic systems - Zhezhera, A.I.; Chmyga, A.A.; Deshko, G.N.; Kozachek, A.S.; Komarov, A.D.; Krupnik, L.I.; Khrebtov, S.M. (Вопросы атомной науки и техники, 2016)
This paper describes the new version of electronic control unit for ion beam forming in the Heavy Ion Beam Probing (HIBP) diagnostics. This improved unit was developed, manufactured, installed and tested on HIBP system for Uragan-2M torsatron. Some new schematic solutions that are implemented in this unit were created as the result of long-term work with various types of injector power supplies and their control systems, installed on HIBP diagnostics for different fusion devices. The new advanced and highly efficient electronic control block has been constructed. It provides all the necessary functions for adjusting the parameters of the ion beam as well as handy and stable operation of the injector in the experiments on Uragan-2M torsatron.